School sport, one of the pillars of South-South cooperation between Morocco and African countries: School sport, one of the pillars of South-South cooperation between Morocco and African countries - ZAHIR , Nezha (African Scientific Journal, 2021)
Investing in youth through school sport is one of the axes of the South-South Cooperation Strategy adopted by the Kingdom of Morocco in its relations with the countries of the African Continent, and this in accordance with the Royal vision which aims for growth economic and human development in Africa. Sport is at the center of the concerns of international institutions such as the United Nations. It is also an important factor in achieving the objectives of sustainable development, in particular the 4th objective relating to quality education. Thus, sport becomes an institution and identity necessity in the new development model of African countries to equip African youth with the skills of the 21st century. The Moroccan strategy to develop African school sport has been seen in the dynamics established at the continental level and in the various actions carried out by our country to give it its deserved place at the international level. Among the flagship actions, there is the organization of the Gymnasiade[1] 2018, as well as the first and second African school sport forums. At the institutional level, Morocco holds the Vice-Presidency of the International School Sport Federation and the Presidency of the African School Sport Federation. It is in this context that our article aims, through an exploratory and documentary study, to highlight the efforts made by Morocco to promote African school sport and to propose levers for the development of Moroccan leadership in this field. [1] Gymnasiade or Olympic school sport games are a multi-sport competition reserved for under 18s, organized by the international federation of school sport, every 4 years since 1974.